A theoretical examination of known and hypothetical clathrate hydrate materials - Tribello, GA; Slater, B (AMER INST PHYSICS, 2009)
The recent synthesis of a new hydrogen binary hydrate with the sH structure has highlighted the potential storage capabilities of water clathrates [T. A. Strobel, C. A. Koh, and E. D. Sloan, J. Phys. Chem. B 112, 1885 (2008) and A. R. C. Duarte, A. Shariati, L. J. Rovetto, and C. J. Peters, J. Phys. Chem. B 112, 1888 (2008)]. In this work, the absorption of hydrogen and the promoters used in the experimental work are considered using a simplified model for the host-guest interaction, which allows one to understand the stabilizing effects of multiple help molecules. Two further hypothetical clathrates, which are isostructural with known zeolite structures, are also investigated. It is shown that the energy gained by absorbing adamantane into these two frameworks is far greater than that gained upon absorption of adamantane into the sH structure. Hence, a clathrate with the same topology as the DDR (Sigma 1) zeolite may be synthesizable with adamantane and hydrogen as guest molecules as, in the conditions explored here, this phase appears to be more stable than the sH structure. (C) 2009 American Institute of Physics. [DOI:10.1063/1.3142503]